Book selection for shared reading: Parents' considerations and researchers' views. (September 2019) - Bergman Deitcher, Deborah; Aram, Dorit; Adar, Gali
This qualitative study explores parents' considerations in selecting narrative picturebooks to read with their children. Participants included 104 middle-socioeconomic status parents (84 mothers, 20 fathers) of young children (51 boys, 53 girls; M age = 61.26, SD = 9.52). We presented parents with two translated children's books whose content was previously unfamiliar to them: Maurice Sendak's Where the Wild Things Are (1991) and Julia Donaldson's Where's My Mom? (2008). A semi-structured interview stimulated the conversation surrounding what parents consider is a good book to read to their children, what they like in a good children's book, and why. Parents' responses highlighted some main considerations: purpose behind their reading, illustrations, centrality of the written text and structure. We highlight how these elements are similar to and different from those that have emerged from research in children's development, literacy and literature, and recommend how parents, practitioners and the research community can dialogue in ways that may enhance adult–child book interactions.